The British Gynaecological Cancer Society Delphi Consultation Exercise on Expected Standards of Practice for Doctors Specializing in the Area of Gynecological Oncology. Issue 4 (1st May 2010) - Moss, Esther L.; Owen, Geraint; Jones, Peter W.; Sarhanis, Panos; Nordin, Andrew; Luesley, David; Redman, Charles W.E.
Abstract : Objective: To determine a set of auditable standards applicable to physicians working in the area of gynecological oncology, which could be implemented as accreditation criteria for the revalidation procedure. Design: A 3-round Delphi consultation exercise. Setting: British Gynaecological Cancer Society (BGCS) members and delegates at the 2006 and 2007 Annual BGCS conferences Population 35 BGCS members, 72 delegates attending the 2006 BGCS conference and 120 delegates attending the 2007 conference. Methods: A preliminary Delphi consultation of members was performed electronically to determine the contents of the final Delphi questionnaires. Prioritization was achieved by scoring each parameter on a 5-point Likert scale. Main Outcome Measure: The mean score awarded to each benchmarking parameter and the identification of parameters scoring 4 or above 75% or more of the respondents. Results: The first round contained responses from 68 participants in stage 1 and 72 in stage 2. The second round included 120 participants. Nine of the auditable standards in first round and 10 in the second round achieved a score of 4 or above 75% or more of the participants and were therefore considered to be essential for revalidation. The selected criteria focused on an individual clinician's caseload and performance, multidisciplinary team working and continued professional development. Conclusions: This study has used the Delphi technique to identify auditable standards which could be used in the revalidation process of physicians working in the area of gynecological cancer.